Using the `Test of Economic Competence' with secondary school students in Hong Kong: Results and psychometric properties - Tim Kaiser; Luis Oberrauch; Ming Fai Pang; Günther Seeber (ZBW – Leibniz Information Centre for Economics, 2021)
We administer an adapted version of the Test of Economic Competence (TEC) to a sample of secondary school students in Hong Kong and study the psychometric properties of the adapted scale relative to test statistics based on a sample of German secondary school students. The results indicate adequate psychometric properties of the adapted measurement scale. Reassuringly, we find no evidence of differential item functioning in the adapted test and student-level correlates of economic competence mirror the results from a large-scale assessment in Germany relying on the original scale. Collectively, these results underscore the construct validity of the adapted test and suggest that the adapted TEC may be well suited to study the economic competence of secondary school students in a variety of educational contexts.
Keywords: A21; G53; 330; Pre-college economic education; economic competence; IRT; economic literacy